Electron Anisotropies in Magnetotail Dipolarization Events - Birn, Joachim; Hesse, Michael; Runov, Andrei (Frontiers in Astronomy and Space Sciences, 2022)
Anisotropic electron distributions can be a major source of free energy for the generation of microinstabilities and waves. Here we investigate specifically anisotropies of the suprathermal electrons associated with dipolarization events in the geomagnetic tail. The investigation is based on an MHD simulation of magnetotail reconnection, flow bursts and dipolarization. This simulation is used to trace test particles in the electromagnetic fields of the MHD simulation and investigate their acceleration and contributions to flux increases. The simulated velocity distributions yield anisotropies which can be dominantly parallel ("cigar"-shaped), perpendicular ("pancake"-shaped) to the magnetic field, or a combination thereof (e.g., "rolling-pin"-shaped), depending on location, relative timing, and energy.